A motion-responsive injectable lubricative hydrogel for efficient Achilles tendon adhesion prevention - Shujie Cheng; Jihong Yang; Jianguo Song; Xin Cao; Bowen Zhou; Lan Yang; Chong Li; Yi Wang (Materials Today Bio)
Achilles tendon is a motor organ that is prone to tissue adhesion during its repair process after rupture. Therefore, developing motion-responsive and anti-adhesive biomaterials is an important need for the repair of Achilles tendon rupture. Here, we report an injectable lubricative hydrogel (ILH) based on hydration lubrication mechanism, which is also motion-responsive based on sol-gel reversible transmission. The lubrication performance is achieved by zwitterionic polymers as we previously proved, and the sol-gel reversible transmission is enabled by dynamic disulfide bonds. Firstly, ILH was proved to be successfully prepared and lubricated as well as sol-gel reversible via FTIR characterization, rheological measurement and tribological tests. Then, in vitro cell experiments and coagulation tests demonstrated the optimal cytocompatibility and hemocompatibility of ILH. To evaluate the potential of ILH's biofunction in vivo, SD rats' Achilles tendon rupture & repair model was established. The animal experiments' results showed that ILH significantly prevented tendon adhesion and thus promote tendon healing by inhibiting TGFβ1-Smad2/3 pathway. We believe this work will open a new horizon for tendon adhesion-free repair.